Analisis Pengaruh Diskon Harga, Bonus Pack Dan Pendapatan Konsumen Terhadap Keputusan Pembelian Impulsif Pada Konsumen Supermarket CarrefourDi Surakarta - , Nabilah; , Drs. M. Nasir, MM (2017)
The purpose of this study to examine the effect of price discounts on purchasing behavior implusif. To test the effect of the bonus pack buying behavior implusif. To test the effect of the income of consumers against impulsive buying behavior. Sample was taken using accidental sampling. So we can conclude that the respondent samples will be taken in this study were 100 respondents with criteria that respondents who do impulse purchases at Carrefour Supermarket Surakarta. Be at least 16 years old and Gender male and female. Based on the results of this research note that the analysis of the t test known variables significantly influence the price discount impulsive buying decisions. Variable bonus pack has a significant influence on purchasing decisions impulsively. 2 Variable income has a significant influence on purchasing decisions impulsively. F-test analysis results are known discount price variable (X1), bonus pack (X2), income (X3) jointly and significant impact on impulsive buying decisions (Y). The results of test analysis coefficient of determination (R2) obtained result Adjusted R square (R2) of 0.315, meaning variation changes can dijelskan purchase decision variable by variable price discount (X1), bonus pack (X2), income (X3) of 31.5% , While the remaining 68.5% is explained by other variables outside the model.